A Study on Destination Loyalty of Tourists at the UNESCO World Heritage Site : A Case Study of Old Goa in India - Mishra, Rajiv; Singh, Vikas; Mishra, Namrata (Prabandhan: Indian Journal of Management, 2022)
This study investigated the factors influencing tourist destination loyalty towards the UNESCO World Heritage Site of Old Goa. This study used a quantitative research approach to collect the information from the tourists at the heritage site. Three hundred ninety respondents participated in the survey. Further, exploratory factor analysis (EFA) revealed three factors, that is, Site Attributes (SA), Accessibility and Transportation Facilities (ATF), and Destination Amenities (DA). Moreover, the findings of this study conducted at the heritage site also showed a high level of overall satisfaction among the visiting tourists. According to the findings of linear regression, there was a strong positive link between the selected destination features and visitors’ destination loyalty. An importance-performance analysis (IPA) was performed in the study to assess the destination’s significant strengths and shortcomings. Understanding the underlying factors that lead to tourists’ loyalty is expected to offer the necessary insights for destination managers to espouse destination management and marketing strategies.